PENDIDIKAN ISLAM MULTIKULTURAL BERWAWASAN WASATHIYAH: Penguatan Karakter wasathiyah Santri Patriot Panji Pelopor - Masykuri, Masykuri; Qodriyah, Khadijatul; Bz, Zakiyah (JURNAL ISLAM NUSANTARA, 2020)
This article describes wasathiyah-minded multicultural Islamic Education: strengthening the character wasathiyah sanytri Patriot panji Pelopor of Pondok Pesantren nurul Jadid Paiton Probolinggo dormitory. Providing education and understanding about multicultural Islamic education with wasathiyah insight as a strengthening of student character is one of the efforts for students to have multiculturalism and patterned thinking and behave moderation as santri and as citizens in general. The islamic base of wasathiyah orderedtren through the education of multicultural Islamic education is expected to be a character that is rooted in every student of mission / santri and human beings in general, and has a complete awareness in the realm of religious awareness, scientific awareness, public awareness, national and state awareness and organizational awareness. Conceptualized in the trilogy and the awareness of pondok Pesantren Nurul Jadid Probolinggo. This research uses qualitatively described method by data collection using wawanvara, dokuntasi and obsesvasi techniques. This research was carried out in the dormitory of Santri Patriot Panji Pelopor of Pondok pesantren Nurul jadid. This research also describes the process of development of balance, curriculum and scientific transformation process.Â